PENINGKATAN KEMAMPUAN KOMUNIKASI SISWA KELAS XI MAN I KOTA CIREBON MELALUI PENERAPAN MODEL RECIPROCAL TEACHING - Nur Fajrin; Sumliyah Sumliyah; Rifqi Hidayat (Integral : Pendidikan Matematika, 2018)
The research is based on the law of comunacition mathematical and mathematical disposition and the less of the students’s activation in learning process. The research objective is to know the improvement of ccomunication mathematical which the learning process used is Reciprocal Teaching learning model with conventional learning. The research is Quasi Experimental research.The research design is used Nonequivalent Control Group Design and sample collection technique is Sampling Purposive .The population in the research is the students of class XIth MAN I Kota Cirebon, academic year 2017/2018. The sample of the research is the XIth qraders 39 th student class XIth A is classes eksperimental and 39 th student class XIth B is classes control. Based on the result the difference of the average using of N-gain using the test of Independent Sample t-test equals sig score (1 tiled) 0,0005 < 0,05 means H0 rejected. On the other hard, based on the result of questionnaire using the test of Mann Whitney U-Test eguals Asymp. Sig(2 tailed) 0,000 < 0,5 means H0 rejected. The research result shows that: The improvement of communication mathematical which is using Reciprocal Teaching learning model is better than the students who are learning by conventional learning process. Key Words: Mathematical Disposition, Comunication Mathematical, Reciprocal Teaching.